The impact of nonsurgical periodontal treatment on oral health-related quality of life: a systematic review and meta-analysis (2020)
Objective To estimate the impact of nonsurgical periodontal treatment (NSPT) on patients’ oral health-related quality of life (OHRQoL). The focused question for this systematic review was: in adults patients with periodontitis, does NSPT improve oral health-related quality of life? Material and methods Five databases (PubMed, CIHNL, EMBASE, LILACS and CENTRAL) were searched up to April 2019 (PROSPERO CRD42018103393). Intervention trials and cohort studies assessing the OHRQoL data of adults with periodontitis, enduring non-surgical periodontal treatment (NSPT) were eligible for inclusion. Subgroup random-effects meta-analysis was conducted methodically. Results Overall, 491 studies were retrieved, out of which 19 met the inclusion criteria. Two randomized clinical trials (RCTs) and ten cohort studies were further analysed. Seven cohort studies were included in the statistical analysis. Subgroup meta-analyses of cohort studies revealed that NSPT improves in average 2.49 (95% CI 0.95–4.02), 8.94 (95% CI 6.89–10.99) and 6.49 (95% CI 5.11–7.88) OHRQoL levels at 1–2 weeks, 3–4 weeks and 6–12 weeks of post-treatment, respectively. Conclusions NSPT procedures greatly improve the oral health-related quality of life within a short time, remaining stable after 3 months of treatment. Clinical relevance This systematic review brings forward summary evidence that NSPT improves the OHRQoL in adults with periodontitis from a patient-centred perception and remain stable in the short term.